Stock Market Predictability and Industrial Metal Returns - Jacobsen, Ben; Marshall, Ben R.; Visaltanachoti, Nuttawat (Management Science, 2019)
Price movements in industrial metals such as copper and aluminum predict stock returns. Increasing industrial metal prices are good news for equity markets in recessions and bad news in expansions. A one-standard-deviation increase in industrial metal returns predicts a price drop of one and a half percent in monthly stock market returns in expansions and an increase of around a half percent during recessions. The predictability is distinct to and compares favorably with that from more established predictors. This paper was accepted by Lauren Cohen, finance.